Answer:
[tex]x= \dfrac{3-2x}{4-3x}[/tex]
Step-by-step explanation:
Given:
[tex]x=\dfrac{1}{2-\dfrac{1}{2-\dfrac{1}{2-x}}}}[/tex]
Simplify:
[tex]\begin{aligned}2-\dfrac{1}{2-x} & =\dfrac{2(2-x)-1}{2-x}\\\\ & =\dfrac{3-2x}{2-x}\end{alilgned}[/tex]
Therefore:
[tex]x=\dfrac{1}{2-\dfrac{1}{\dfrac{3-2x}{2-x}}}[/tex]
Simplify:
[tex]\begin{aligned}2-\dfrac{1}{\dfrac{3-2x}{2-x}} & =2-\dfrac{2-x}{3-2x}\\\\ & =\dfrac{2(3-2x)-(2-x)}{3-2x}\\\\ & = \dfrac{6-4x-2+x}{3-2x}\\\\ & = \dfrac{4-3x}{3-2x}\end{aligned}[/tex]
Therefore:
[tex]x & =\dfrac{1}{\dfrac{4-3x}{3-2x}}[/tex]
[tex]\textsf{Apply the fraction rule}: \quad \dfrac{1}{\frac{b}{c}}=\dfrac{c}{b}[/tex]
[tex]\implies x& = \dfrac{3-2x}{4-3x}[/tex]